2010
DOI: 10.1111/j.1398-9995.2010.02438.x
|View full text |Cite
|
Sign up to set email alerts
|

The I/D polymorphism of angiotensin-converting enzyme gene and asthma risk: a meta-analysis

Abstract: This meta-analysis suggested that the I/D polymorphism of ACE gene would be a risk factor of asthma. To further evaluate gene-to-gene and gene-to-environment interactions between polymorphisms of ACE gene and asthma risk, more studies with large groups of patients are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 27 publications
0
28
2
Order By: Relevance
“…Davin et al (12) reported that the incidence of increased plasma IgE levels relative to age-matched normal values was significantly higher among HSP patients, indicating that IgE may play a pathogenic role in HSP. IL-5 induces B-cell immunoglobulin class switching to IgA and also activates eosinophils (22)(23)(24). HSP has previously been considered an IgA-mediated vasculitis (1).…”
Section: Hsp In Allergic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Davin et al (12) reported that the incidence of increased plasma IgE levels relative to age-matched normal values was significantly higher among HSP patients, indicating that IgE may play a pathogenic role in HSP. IL-5 induces B-cell immunoglobulin class switching to IgA and also activates eosinophils (22)(23)(24). HSP has previously been considered an IgA-mediated vasculitis (1).…”
Section: Hsp In Allergic Diseasesmentioning
confidence: 99%
“…Epidemiological data reveal that the prevalence of Th1-mediated autoimmune diseases has been rising in parallel with Th2-mediated allergic diseases worldwide over the past two decades (21)(22)(23). The hygiene hypothesis suggests that early-life infections and microbial exposures may protect against the development of allergy and autoimmune diseases, as a potential explanation for the increased occurrence of allergic and autoimmune diseases (24)(25)(26). In our previous population-based cohort studies, we found increased incidence and risk of systemic lupus erythematosus (SLE) in children with atopic dermatitis and asthma (27,28).…”
Section: Hsp In Allergic Diseasesmentioning
confidence: 99%
“…Deviation from Hardy-Weinberg equilibrium (HWE) for the distribution of the allele frequencies was analyzed by Fisher exact test in control groups [17]. Odds ratios (ORs) corresponding to a 95% confidence interval (CI) were applied to evaluate the strength of association of VDR polymorphisms with CAD risk; ORs were calculated according to the method of Woolf [18].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, PTB is a complex disease that results from the infection with Mycobacterium TB and genetic susceptibility. These differences in genetic susceptibility may also result from individual status or other factors (Zhang et al, 2010). Thus, further studies are needed to assess the effect of additional interactions in different ethnicities and to validate our results.…”
Section: Discussionmentioning
confidence: 99%